The impact, utility and efficiency of screening and consultation processes within the Offender Personality Disorder Pathway - AISLING O'MEARA (2023)
The Offender Personality Disorder Pathway (OPDP) is a jointly commissioned programme of psychological interventions and services delivered into His Majesty’s Prison and Probation Service (HMPPS) by National Health Service (NHS) staff. There are two target groups for OPDP intervention services - high risk of harm violent and sexual offenders who present with complex personalitydifficulties likely to indicate the presence of personality disorder; and the prison and probation staff who are responsible for these individuals. This thesis was commissioned by the OPDP central programme to evaluate key frontline elements of the OPDP delivery – a review of the evidence of core OPDP delivery; the methods by which individuals are identified as eligible for OPDP intervention(with an initial focus on women); and the impact and process of psychological consultation with probation staff. A systematic review of the published literature on the impact of core OPDP community delivery on the four outcomes underpinning the programme was conducted in order to inform the evidence of effectiveness for this element of the programme. OPDP identification was evaluated through a multi-stage and multi-method quantitative analysis of all female offenders and used predictive modelling to devise a revised method of identification. Finally, consultation processes were explored at a single region level using a two-stage data gathering process and employing content analysis to explore the key functions of consultations. Findings from all three studies are discussed in relation to the ongoing development of this programme and avenues for further exploration.